Exploration and Analysis on the Psychological Capital of Entrepreneurship and the Deviant Innovation Behavior of Employees - Gao, Qianying; Xu, Jing; Tao, Zhe; Liu, Li; Wu, Cisheng (Frontiers in Psychology, 2020)
This study aims to explore the psychological capital of entrepreneurship and the deviant innovation behavior of employees, thereby providing theoretical support for the implementation of Chinese innovation policy. By analyzing the previous research results, this study used questionnaires to collect the required data for exploration. Two questionnaires were designed: one was a survey for the psychological capital of entrepreneurship, and the other was a survey for deviant innovation behavior of employees. The research results show that the correlation coefficient between entrepreneurial performance and entrepreneurial psychological capital is 0.29, indicating that there is a significant correlation between entrepreneurial psychological capital and entrepreneurial performance; the correlation coefficient between entrepreneurial opportunity ability and entrepreneurial performance is 0.40, indicating that there is a significant correlation between entrepreneurial opportunity ability and entrepreneurial performance; the correlation coefficient between entrepreneurial psychological capital and entrepreneurial opportunity ability is 0.81, indicating that there is a significant correlation between entrepreneurial psychological capital and entrepreneurial opportunity ability. Besides, there are significant correlations between the work values and psychological empowerment of employees, the work values and deviance innovation of employees, and the psychological empowerment and deviance innovation of employees. The scores of psychological empowerment and work values of employees during the period of low emotional intelligence show a downward trend, while the scores of the psychological empowerment of employees increase significantly when they show high emotional intelligence, and the differences are statistically significant. When task interdependence is high, the psychological empowerment and deviance innovation scores of employees are lower, and the difference is statistically significant. For this purpose, this study enriches the research on psychological capital and deviant innovation and provides a reference for the practice of innovation management.